Kemampuan Pemecahan Masalah Matematis Topik PLSV Pendekatan Pemodelan Matematika Menggunakan Media Pembelajaran Berbasis ICT - Syabillah, Dinda; Kurniadi, Elika; Harini, Bunda; Suganda, Vina Amilia (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
Problem-solving is one aspect of high-level thinking skills that is important for students to have. Problem-solving is closely related to mathematical modeling, this is because mathematical modeling is usually considered the art of applying mathematics to real-world problems. This research is a qualitative descriptive study and the subjects of this study were 32 students of class VII C junior high school number 1 at Pagar Alam. This study aims to determine students' mathematical problem-solving abilities for the one variable linear equation topic with a mathematical modeling approach using ICT-based learning media. Data collection techniques used in this study were written tests and interviews. Based on the results of the study, it was found that learning mathematical modeling using Google Sites media was able to make a significant contribution to the problem-solving abilities of senior high school number 1 at Pagar Alam students. The results of the achievement of problem-solving abilities of VII C students with an average of 53.90% are categorized as sufficient. Students are more interested in using mathematical modeling learning using Google Sites.